Inhibition of energy metabolism in macrophages to block MPS for enhancing the chemotherapy efficacy - Bin, Li; Huang, Linlin; Chen, Aiyu; Yang, Yinyi; Zheng, Yanmei; Zhang, Hanwen; Zhang, Qinfang; Zheng, Jiahui; Qiu, Meiting; Li, Xiajin; Tan, Yangbo (Frontiers in Bioengineering and Biotechnology, 2025)
Various biological barriers hinder the effective use of administered nanoparticles, with the mononuclear phagocyte system (MPS) being a major obstacle to their in vivo efficacy. Glucose metabolism is an important factor for macrophages to perform MPS clearance in vivo. In this study, energy metabolism-blocking nanoparticles PEG-S-S-PLA@RGD @Dox@BAY876 (RPDB NPs) were developed to change drug distribution in the body, improving the efficacy of chemotherapy. First, BAY876 showed an excellent inhibition effects on macrophage energy metabolism in vitro. This inhibitory behavior of energy metabolism reduced the aggregation of nanoparticles in macrophages. Similarly, the migration capacity of macrophages was also limited by reduced energy metabolism. Second, the fluorescence distribution in the mice also showed that the fluorescence intensity of RPDB NPs in the liver was about 40% of that of RPD NPs, suggesting that reducing energy metabolism helps to downregulate the uptake of mononuclear phagocytic cell (MPS), and change the distribution of the drug in vivo. Furthermore, anti-tumor effects of RPDB NPs were evaluated both in vivo and in vitro. In vivo, RPDB nanomicelles inhibited breast cancer by up to 68.3%, higher than other administration groups. Moreover, the pathological section of tumor exhibited a significantly greater increase in cell apoptosis in RPDB NPs group. Hence, inhibition of macrophage energy metabolism is a promising approach to eliminate MPS effects, while also opening up a new window for the effective inhibition of tumors development and metastasis.